Deep incorporation of organic amendments into soils of a ‘Calardis Musqué’ vineyard: effects on greenhouse gas emissions, vine vigor, and grape quality - Schneider, Nele; Islam, Muhammad; Wehrle, Ralf; Pätzold, Stefan; Brüggemann, Nicolas; Töpfer, Reinhard; Herzog, Katja (Frontiers in Plant Science, 2023)
Traditional wine growing regions are more and moreincreasingly endangered by climatic alterations. One promising approach to mitigate advancing climate change could be an increase of soil organic matter. Here, especially subsoils are of interest as they provide higher carbon storage potential than topsoils. In this context, vineyard subsoils could be particularly suitable since they are deeply cultivated once before planting and afterwards, left at rest for several decades due to the perennial nature of grapevines. For this purpose, a biochar compost substrate and greenwaste compost were incorporated in up to 0.6 m depth before planting a new experimental vineyard with the fungusresistant grapevine cultivar 'Calardis Musqué'. The influence of this deep incorporation on greenhouse gas emissions and grapevine performance was evaluated and compared to a non-amended control using sensor-based analyses. Higher Increased CO2 emissions and lower N2O emissions were found for the incorporation treatments compared to the control, but these differences were not statistically significant due to high spatial variability. Only few of the plant traits like chlorophyll content or berry cuticle characteristics were significantly affected in some of the experimental years. Over the course of the study, annual climatic conditions had a much stronger influence on plant vitality vigor and grape quality than the incorporated organic amendments. In summary, organic soil amendments and their deep incorporation did not have any significant effect on greenhouse gas emissions and no measurable or only negligible effect on grapevine vitalityvigor, and grape quality parameters. Thus, according to our study the deposition of organic amendments in vineyard subsoils seems to be an option for viticulture to contribute to carbon sequestration storage in soils in order to mitigate climate change.